Benign duodenocolic fistula: a rare complication of peptic ulcer disease - Alexander F. Cahoon; Leila C. Tou; Abimbola T. Adenote; Drew J. Triplett; Mustafa Musleh (European Journal of Case Reports in Internal Medicine, 2025)
Background: Duodenocolic fistulas are uncommon but serious complications of peptic ulcer disease (PUD), resulting from the erosion of a duodenal ulcer into the colon. This connection typically forms when a chronic ulcer perforates or penetrates through the duodenum, leading to inflammation and necrosis that disrupts the normal anatomical barriers. Case Report: A 66-year-old male with a history of inadequate medical follow-up, chronic nonsteroidal anti-inflammatory drug use, alcohol use disorder, and PUD, developed a duodenocolic fistula secondary to a perforated duodenal ulcer. Endoscopy revealed a large duodenal ulcer with fistulisation into the colon. The patient underwent definitive surgical treatment, including fistula takedown, partial colectomy, antrectomy, and gastrojejunostomy. Conclusion: This case highlights the importance of early recognition and thorough evaluation of duodenocolic fistulas, which can lead to severe complications such as sepsis, malnutrition, and gastrointestinal bleeding. While conservative management may be appropriate in select cases, surgical intervention remains the definitive treatment for symptomatic or complicated fistulas. Prevention through targeted interventions, such as effective management of PUD and routine screening for high-risk conditions, is crucial. A multidisciplinary approach is essential for accurate diagnosis and individualized treatment of duodenocolic fistulas.